2005
DOI: 10.3727/000000005783982620
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Repeat Regeneration Potential of the Engineered Liver Tissues under the Kidney Capsule in Mice

Abstract: Liver tissue engineering using hepatocyte transplantation has been proposed as a therapeutic alternative to liver transplantation toward several liver diseases. We have previously reported that stable liver tissue with the potential for liver regeneration can be engineered at extrahepatic sites by transplanting mature hepatocytes into an extracellular matrix. The present study was aimed at assessing the liver tissue persistence after induced regeneration by hepatectomy and repeat regeneration potential induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…In our previous reports, significantly higher hepatocyte survival was achieved when human or mouse hepatocytes were cotransplanted with EHS-ECMs at heterotopic sites as compared to hepatocytes without ECMs. 1,4,5 In line with these data, significantly higher and sustained survivals were achieved in group 2 (hepatocytes with EHS-ECMs) compared with the survival of hepatocytes alone (group 1). When hepatocytes were transplanted with growth factor-reduced EHS-ECMs (group 3), sustained survival was also achieved with no difference in survival compared to group 2.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…In our previous reports, significantly higher hepatocyte survival was achieved when human or mouse hepatocytes were cotransplanted with EHS-ECMs at heterotopic sites as compared to hepatocytes without ECMs. 1,4,5 In line with these data, significantly higher and sustained survivals were achieved in group 2 (hepatocytes with EHS-ECMs) compared with the survival of hepatocytes alone (group 1). When hepatocytes were transplanted with growth factor-reduced EHS-ECMs (group 3), sustained survival was also achieved with no difference in survival compared to group 2.…”
Section: Resultssupporting
confidence: 70%
“…Since the marker protein of the transplanted hepatocytes, hAAT, demonstrates a short half-life (less than 2 hours) in the mouse 7 and is produced only from the hepatocytes, the viability and survival of the transplanted hepatocytes in vivo can reasonably be assessed by periodic mouse serum measurement of the hAAT reporter protein, as described previously. [3][4][5][6][7] Mice were sacrificed at day 140; the grafts were excised and processed for histological examination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using primary hepatocytes, our group has developed several innovative approaches to create a functional liver system under the kidney capsule or in subcutaneous locations (13,15,16,24,25), and we have clearly demonstrated that these ectopically engrafted hepatocytes also possess the ability for proliferation (13,16,26). This would be a significant benefit in the use of these hepatocytes, because most of the adult hemophilia B patients presented with chronic hepatitis B and/or C viral infection as a result of treatments with blood-borne contaminated plasma-derived FIX concentrates.…”
mentioning
confidence: 99%
“…Hepatocytes were isolated from C57Bl/6 wild-type mice using a collagenase perfusion method as previously described (13)(14)(15)(16). The recipient FIX knock-out (FIX-KO) mice, syngeneic to donor mice (17), were transplanted with the isolated hepatocytes (1.5ϫ10 6 cells in 200 L) into the liver through the inferior pole of the spleen (nϭ25).…”
mentioning
confidence: 99%